2021
DOI: 10.5944/openpraxis.13.1.1187
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Student Perceptions as Co-authors of Course Material

Abstract: Students acting as co-creators of academic material is growing in popularity as a pedagogical approach in higher education. With student engagement and persistence consistently being emphasized for student and institution well-being, educational praxis must foster engaged, high-retention student cohorts. This exploratory research uses a mixed-methods approach to examine the experience of students participating in a first-year course utilizing OER-enabled Pedagogy. Students considered how projects that were ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 8 publications
6
23
1
Order By: Relevance
“…Students also indicated agreement that their photographs contributed to the diversity of publicly available materials. Consistent with previous studies (Baran & Al Zoubi, 2020;Hilton et al, 2019;Hollister, 2020;Werth & Williams, 2021), students reported a moderate level of concern about their project being publicly available, in general (M = 3.0, SD = 1.37, range 1-5). However, they also had a fair level of agreement that they liked sharing their photos with their classmates (M = 3.94, SD = 1.24, range 1-5) and the public (M = 3.94, SD = 1.26, range 1-5).…”
Section: Student Perceptions Of the Open Pedagogysupporting
confidence: 86%
See 2 more Smart Citations
“…Students also indicated agreement that their photographs contributed to the diversity of publicly available materials. Consistent with previous studies (Baran & Al Zoubi, 2020;Hilton et al, 2019;Hollister, 2020;Werth & Williams, 2021), students reported a moderate level of concern about their project being publicly available, in general (M = 3.0, SD = 1.37, range 1-5). However, they also had a fair level of agreement that they liked sharing their photos with their classmates (M = 3.94, SD = 1.24, range 1-5) and the public (M = 3.94, SD = 1.26, range 1-5).…”
Section: Student Perceptions Of the Open Pedagogysupporting
confidence: 86%
“…The majority of the questions were on 5-point Likert scales with three open-ended questions included as well. There were 11 Likert-scale questions on instructional material motivation (based on Loorbach et al, 2015), 10 Likert-scale questions on student perceptions of self (based on S. C. Hutton, 2020), 11 Likert-scale questions on student perception of open pedagogy (based on Werth & Williams, 2021), five Likert-scale questions and three check-all-that-apply questions on student perception of the specific Photovoice project (based on Hollister, 2020), and five Likert-scale plus three open-ended questions that were developed by the investigators specifically for this study. Several questions from the survey can be found in Tables 1 and 2; the full student survey can be found on Open Science Framework (Biddle, 2023).…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…This confidence and feelings that the students can contribute to knowledge both in education and in their future professional fields, can build in learners an approach of inquiring and questioning knowledge more effectively, despite their socio-economic background.Similarly, students' affective engagement is also promoted through use of open educational resources. For example,Afolabi (2017) showed how such resources are seen as an advantage by students, who particularly agreed with statements such as they "makes learning more meaningful" and they are "a positive innovation" (p. 117) Werth and Williams (2021). also qualitatively investigated the effect of pedagogy informed by open educational resources on students' motivation and engagement with students' learning.…”
mentioning
confidence: 88%
“…DeRosa and Robison (2017) note that using open pedagogy moves learning to a student-centred approach by shifting the concept of knowledge from something static to a socially-developed construct in which students may participate. Recent studies indicate that OER-enabled pedagogy may impact a variety of other educational outcomes, such as student creativity, involvement in their own learning, grades, self-directed motivation, student engagement, and skill acquisition (Tillinghast, 2020;Werth & Williams, 2021a, 2021bWiley et al, 2017).…”
Section: Student Empowerment and Oer-enabled Pedagogymentioning
confidence: 99%